Organic peroxide market forecast to be worth US$1.20 billion by 2025. Issue 2 (February 2018) - Unknown
Abstract : According to a new report published by Grand View Research (GVR), the global organic peroxide market was valued at US$834.5 million in 2016 and is expected to reach US$1.20 billion by 2025, at a compound annual growth rate (CAGR) of 4.3% between 2017 and 2025. Rising consumer preference for designer clothing as well as increasing global demand for polymers are expected to remain crucial factors for the growth of the organic peroxides sector.